Sustainability, growth, and poverty alleviation: research and policy issues for tropical moist forests - Vosti, Stephen A. (1995)
This chapter examines the complex issues associated with the critical triangle created by the links among agricultural growth, poverty alleviation, and the sustainable use of natural resources, and the factors that condition these links.